2016
DOI: 10.1371/journal.pone.0159848
|View full text |Cite
|
Sign up to set email alerts
|

An Improved FFR Design with a Ventilation Fan: CFD Simulation and Validation

Abstract: This article presents an improved Filtering Facepiece Respirator (FFR) designed to increase the comfort of wearers during low-moderate work. The improved FFR aims to lower the deadspace temperature and CO2 level by an active ventilation fan. The reversing modeling is used to build the 3D geometric model of this FFR; the Computational Fluid Dynamics (CFD) simulation is then introduced to investigate the flow field. Based on the simulation result, the ventilation fan of the improved FFR can fit the flow field we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In contrast, wearing the mask with operational Micro Ventilator brought FICO 2 levels for both activities closer to baseline levels obtained in children not wearing the mask. Computational Fluid Dynamics (CFD) simulation experiments conducted in adult subjects have demonstrated that the introduction of a ventilation fan to the N95 mask is a feasible option for reducing CO 2 accumulation in the dead space of the mask and also for controlling the temperature of the air within the dead space (21,22). The clinical study [Goh YTD, Mun MW, Lee WLJ, et al A randomised clinical trial to evaluate the safety, fit, comfort of a novel N95 mask in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, wearing the mask with operational Micro Ventilator brought FICO 2 levels for both activities closer to baseline levels obtained in children not wearing the mask. Computational Fluid Dynamics (CFD) simulation experiments conducted in adult subjects have demonstrated that the introduction of a ventilation fan to the N95 mask is a feasible option for reducing CO 2 accumulation in the dead space of the mask and also for controlling the temperature of the air within the dead space (21,22). The clinical study [Goh YTD, Mun MW, Lee WLJ, et al A randomised clinical trial to evaluate the safety, fit, comfort of a novel N95 mask in children.…”
Section: Discussionmentioning
confidence: 99%
“…(submitted for publication)] confirmed the earlier CFD studies indicating reduction of CO 2 in the dead space of the mask with operational ventilator fan. Furthermore, CFD studies performed in adult subjects have demonstrated reduction in heat, CO 2 , and moisture build-up within N95 masks configured with operational ventilator fans (21,22). Moisture build-up in N95 masks used in high humidity atmospheres has been shown to reduce filtration efficiency of the masks for Ebola-Makona virus (23).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of the MF as an optional device for better air exchange and reducing heat and moisture build up, when needed, is also one of the recommendations of the Project BREATHE 28 . Earlier simulation experiments done in adult subjects have demonstrated that the introduction of the fan to the N95 mask is a feasible option to reduce the CO 2 accumulation in the dead space and also to control the temperature 36 .…”
Section: Discussionmentioning
confidence: 99%
“…A three-dimension geometric model of a head wearing an N95 FFR is shown in Fig. 1 , which is based on our previous study 11 . Computing meshes of the fluid domain generated by ANSYS ICEM CFD 14.0 is shown in Fig.…”
Section: Cfd Modeling Of Water Vapor Condensationmentioning
confidence: 99%